A Global Synthesis of the Correspondence Between Epizoic Barnacles and Their Sea Turtle Hosts. Issue 1 (5th February 2021) - Zardus, John D
Synopsis: Barnacles that are obligate epizoites of sea turtles are not parasites in the traditional sense. However, they can impair their hosts in some instances, disqualifying the association as strictly commensal. Characterizing these interactions requires knowing which epibionts pair with which hosts, but records of barnacles from sea turtles are scattered and symbiont/host match-ups remain equivocal. The objective of this study was to collate global records on the occurrence of barnacles with sea turtles and describe each species pair quantitatively. Records reporting barnacles with sea turtles were searched spanning the last 167 years, including grey literature, and findings were enumerated for 30, 580 individual turtles to evaluate prevalence. The data were summarized globally as well as subdivided across six geographic regions to assess constancy of the affiliations. Patterns of partnering were visualized by hierarchical clustering analysis of percent occurrence values for each barnacle/turtle pair and the relative selectivity of each symbiont and susceptibility of each host were evaluated. After adjusting for synonymies and taxonomic inaccuracies, the occurrence of 16 nominal species of barnacles was recorded from all 7 extant sea turtle species. Mostly, barnacles were not specific to single turtle species, partnering on average with three hosts each. Neither were barnacles entirely host-consistent among regions. Three barnacles were common to all sea turtles except leatherbacks. The most common, widespread, and least selective barnacle was Chelonibia testudinaria, the only symbiont of all turtles. Excluding single-record occurrences, the barnacle Stomatolepas transversa was the only single-host associate of any hard-shell sea turtle (the green sea turtle) and Platylepas coriacea and Stomatolepas dermochelys were exclusive associates of leatherback sea turtles. Green sea turtles were the most vulnerable to epibiosis, hosting 13 barnacle species and Kemp's ridley sea turtles were the least, hosting three. Geographically, there was an average of nine barnacle species per world region, with diversity highest in the Pacific Ocean (12 species) and lowest in the Mediterranean Sea (6 species). It is paradoxical that the flexibility of barnacles for multiple host species contrasts with their overall strict specificity for sea turtles, with each symbiont occupying a virtually unique suite of turtle hosts.